Study of Plastic Flow of Aluminum Alloy Using Digital Speckle Photography; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Bochkareva A. V. Anna Valentinovna; Lunev A. G. Alexey Gennadievich; Barannikova S. A.; Zuev L. B. (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen